THE EFFECTIVENESS OF THE SIPRAJA APPLICATION IN SUPPORTING THE IMPLEMENTATION OF E-GOVERNMENT IN BLURU KIDUL VILLAGE, SIDOARJO REGENCY - Adinda Oktavia Cantika Putri; Isnaini Rodiyah (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to evaluate the effectiveness of the SIPRAJA (Sidoarjo Public Service System) application in supporting the implementation of e-government in Bluru Kidul Village, Sidoarjo Regency. Method: A qualitative descriptive approach was employed, with data collected through interviews, observations, and documentation involving service officers and community members as informants. Results: The findings reveal that SIPRAJA has improved accessibility and efficiency in public services, with a significant shift from manual to online submissions. Public satisfaction levels are relatively high, indicating success in providing fast and transparent services. Nonetheless, challenges persist, including limited public understanding of the application’s features and technical disruptions during periods of high demand. Novelty: This study contributes by offering an empirical evaluation of SIPRAJA’s role in advancing village-level e-government, highlighting not only its success in enhancing service delivery but also the critical need for continuous public socialization and infrastructure improvements to ensure sustainable and inclusive digital governance.